2016
DOI: 10.1089/cap.2015.0264
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Long-Term Cardiovascular Effects of Stimulant, Guanfacine, and Combination Therapy for Attention-Deficit/Hyperactivity Disorder

Abstract: Objectives: This study examines cardiovascular (CV) effects of guanfacine immediate-release (GUAN-IR), dexmethylphenidate extended-release (DMPH), and their combination (COMB) during acute and long-term treatment of youth with attention-deficit/hyperactivity disorder. Methods: Two hundred seven participants aged 7-14 years enrolled in an 8-week double-blind randomized trial of GUAN-IR (1-3 milligrams (mg)/day), DMPH (5-20 mg/day), or COMB with fixed-flexible dosing and titrated to optimal behavioral response. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…When children with ADHD are treated with stimulants, they often show an increase of their usually low BP concurrently with symptom improvement [ 51 , 52 , 53 , 54 ]. This clinical observation and additional findings from diurnal heart rate, cortisol level and sleep stages suggest a dysregulation of the autonomic nervous system in children with ADHD and leads to the subcortical (low) arousal hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…When children with ADHD are treated with stimulants, they often show an increase of their usually low BP concurrently with symptom improvement [ 51 , 52 , 53 , 54 ]. This clinical observation and additional findings from diurnal heart rate, cortisol level and sleep stages suggest a dysregulation of the autonomic nervous system in children with ADHD and leads to the subcortical (low) arousal hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, nonstimulants, which are generally less effective and have a slower onset of effect than stimulants [84], are also not without limitations. For example, they have been associated with minor changes in blood pressure or cardiovascular risk [85][86][87], precipitation of secondary mania [88,89], and suicidal ideation [90], although these events are rare and generally restricted to vulnerable populations with pre-existing conditions.…”
Section: Future Of Viloxazine: a Potential New Application In Adhdmentioning
confidence: 99%
“…Indeed, in a comprehensive double-blind, cross-over QT study with 83 healthy adults therapeutic and supra-therapeutic doses (4 mg and 8 mg, respectively) of guanfacine-IR revealed that neither doses of this α2-adrenergic receptor agonist prolonged the QTc interval through 12 h after drug administration [Martin et al 2015]. In addition, a recent double-blind randomized trial assessed the acute and long-term cardiovascular effects of stimulants (d-methylphenidate-XR), guanfacine-IR and their combination in 207 children and adolescents with ADHD, aged 7-14 years [Sayer et al 2016]. The study showed that combination therapy might attenuate the small but statistically significant changes associated with either single treatment.…”
Section: Cardiovascular Safety Of Adhd Pharmacotherapiesmentioning
confidence: 99%
“…However, although commonly mild, time-limited and manageable with dose adjustment, without the need to stop treatment, ADHD pharmacotherapies are not exempt from treatment emergent adverse events (TEAEs), as evidenced in randomized controlled trials [Aagaard and Hansen, 2011; Adler et al 2009; Graham and Coghill, 2008; Upadhyaya et al 2015]. Indeed, treatment discontinuation rates due to adverse events with any of the approved medications for ADHD are generally low [Clavenna and Bonati, 2014; Michelson et al 2003; Sayer et al 2016; Weisler et al 2006].…”
Section: Safety and Tolerability Considerations Of Adhd Medicationsmentioning
confidence: 99%
See 1 more Smart Citation